Genome sequencing and resequencing identified three horizontal gene transfers and uncovered the genetic mechanism on the intraspecies adaptive evolution of Gastrodia elata Blume - Wang, Yunsheng; Shahid, Muhammad Qasim (Frontiers in Plant Science, 2023)
Horizontal gene transfer is a rare and useful genetic mechanism in higher plants. Gastrodia elata Blume (GE) (Orchidaceae), well known as traditional medicinal material in East Asia, adopts a heterotrophic lifestyle, thus being considered to be more prone to horizontal gene transfer (HGT). GE is a “polytypic species” that currently comprised of five recognized forms according to the plant morphology. G. elata Blume forma elata (GEE) and G. elata Bl.f.glauca (GEG) are two common forms that naturally grow in different habitats with difference in altitude and latitude. G. elata Bl.f.viridis (GEV) often occurs sporadically in cultivated populations of GEE and GEG. However, the genetic relationships and genetic mechanism underpinned the divergent ecological adaptations of GEE and GEG have not been revealed. Here, we assembled a chromosome-level draft genome of GEE with 1.04 Gb. Among predicted 17,895 protein coding genes, we identified three HGTs. Meanwhile, we resequenced 10 GEE accessions, nine GEG accessions, and 10 GEV accessions, and identified two independent genetic lineages: GEG_pedigree (GEG individuals and GEV individuals collected from GEG populations) and GEE_pedigree (GEE individuals and GEV individuals collected from GEE populations), which strongly support the taxonomic status of GEE and GEG as subspecies, not as different forms. In highly differentiated genomic regions of GEE_pedigree and GEG_pedigree, three chalcone synthase-encoding genes and one Phox/Bem1p (PB1) domain of encoding Auxin (AUX)/Indoleacetic acid (IAA) were identified in selection sweeping genome regions, which suggested that differentiation between GEE_pedigree and GEG_pedigree was promoted by the selection of genes related to photoresponse and growth and development. Overall, this new genome would be helpful for breeding and utilization of GE and the new findings would deepen the understanding about ecological adaptation and evolution of GE.